Importance of functional classification in the use of carabids for the environmental risk assessment of the GE crops and other agricultural practices - Svobodová, Zdeňka; Skoková Habuštová, Oxana; Spitzer, Lukáš; Sehnal, František (Insect science, 2020)
Carabids (Coleoptera: Carabidae) seem to be suitable bioindicators of the environmental impacts of novel agrotechnologies, including deployment of the genetically engineered (GE) crops. In this article, we describe our effort to employ carabids in the environmental risk assessment (ERA). GE maize MON88017, its near-isogenic hybrid nontreated or treated with the soil insecticide chlorpyrifos, and two reference hybrids were used to compare three different ways how to utilize carabids in ERA. The analysis of abundance of all captured carabids or of the most abundant carabid species did not disclose any differences between the treatments. The analysis based on the categories of functional traits revealed distinct features of some treatments and proved suitable for ERA because it permitted field data transportability in spite of different species compositions. Our results indicate that GE maize has no detrimental environmental effect. On the other hand, we found significant trends toward lower abundance and lower species number (including analysis of all carabid species together) in plots treated with the insecticide, and some tendencies to higher abundance and higher species number in plots sown with the reference hybrid PR38N86. Using functional group indicators allows identification of unintended changes in ecological functions of agroecosystem and comparability across geographies. We recommend data evaluation at the level of the categories of functional traits in ERA of GE crops and other agricultural practices.
Keywords: brouci; Biodiversity; Risk Assessment; insekticidy; Animals; Environmental Biomarkers; Insecticides; Zea mays; hodnocení rizik; dursban; zvířata; Chlorpyrifos; geneticky modifikované rostliny; Coleoptera; Plants, Genetically Modified; biodiverzita; bioindikátory; kukuřice setá